Appearance and explanation: advancements in the evaluation of journalistic information graphics. Issue 3 (2nd July 2016) - Barnes, Spencer R.
Abstract: Visual communication literature maintains that the essential attributes of any journalistic information graphic (infographic) are appearance and explanation, but little research has been conducted to determine how these properties function. This paper offers new approaches to evaluate the efficacy of infographics by examining how appearance and explanation can be quantified and analyzed via three novel measures: aesthetic value, learning efficiency and performance efficiency. A repeated-measures experiment tested the measures against six infographics varying in quality and configuration. Findings suggest that information processing predicates explanation and that explanation makes slightly more of a contribution to one's interaction with an infographic than appearance.